DEVELOPING WRITING DESCRIPTIVE TEXT MATERIALS FOR THE TENTH GRADE STUDENTS OF TOURISM PROGRAM IN SMK NEGERI 1 SIDIKALANG - Devi Fitriani Samsul Bahri; Amrin Saragih (Universitas Negeri Medan, 2018)
This study deals with the developing writing descriptive text for students of vocational school. The objective of the study is to develop the English writing materials to cope with the students’ needs for grade X students of Tourism Program in SMKN 1 Sidikalang for better materials which are appropriate with the students’ need of tourism program. The research was conducted by using Research and Development (R&D) method. The subject of the research was 2017/2018 students of tenth grade of class X UPW 1 at SMKN 1 Sidikalang. The number of the students was 35 students. The data of this study was collected based on the questionnaire analysis, the interview analysis, the experts judgment and selective writing text. Need analysis questionnaire was calculated by using percentage to get the information of students’ need before developing writing text materials particularly descriptive text. Expert judgment data was calculated by using criteria interval of expert judgment to know validity of writing materials which has been developed. The writing materials were in the form of writing text and writing skills which consisted of thirteen tasks. After the data analyzed, it was found that the expert’s judgment result was 4.5which had a very good criteria interval. The result of the research finds that the developed writing materials are relevant which cope with the students’ need and appropriate to be used in teaching and learning.